Fluctuation current in a superconducting ring caused by a thin solenoid. (17th August 2015) - Kuratsuji, Hiroshi; Tsuchida, Satoshi
Abstract: The fluctuating current due to the Cooper pair is calculated for a superconducting ring threaded by a thin magnetic solenoid that is arranged by time-varying flux. The formulation is based on the Fokker-Planck equation derived by the Langevin-type Landau-Ginzburg equation. The statistical average of the fluctuation current is calculated. As a special case, for the equilibrium state, the current shows a critical behavior near the transition point. In the presence of the time-varying flux, the current is calculated to be a highly nonlinear function of the electric field induced by the time variation of the flux, which yields a sort of the Ohmic law in the limit of the weak field.